Solar-powered ejector-based adsorption desalination system integrated with a humidification-dehumidification system. (15th June 2021) - Ali, Ehab S.; Mohammed, Ramy H.; Qasem, Naef A.A.; Zubair, Syed M.; Askalany, Ahmed
Highlights: Solar adsorption desalination plant with humidification and dehumidification and two ejectors is presented. Mathematical energy and cost models are built. The model is validated against the results in the literature. SDWP reaches 98.41 m 3 /ton with a gain output ratio (GOR) of 2.75. Specific water cost could decline to $0.48/m 3 . Abstract: The paper presents an integrated solar-driven desalination plant. It consists of an adsorption desalination (AD), a humidification-dehumidification (HDH) desalination, and two ejectors. The HDH unit reuses the silica gel AD cycle's waste energy to enhance the proposed integrated system's freshwater production rate. Two ejectors are also installed to improve freshwater productivity further. Two configurations are studied: with and without condenser/evaporator heat recovery (HR) circuit. In this regard, mathematical energy and cost models are built to examine the performance of solar-powered hybrid desalination systems installed in Assiut, Egypt, at different operating parameters. The model is validated against the available results in the literature. The solar irradiation, ambient temperature, adsorption cycle time, and HDH air mass flow rate on the cycle performance are studied. The highest freshwater is produced when the ratio between the mass flow rate of feed saline water and the air is about 1.4. When HR is applied, the specific daily water production (SDWP) reaches 83.1 m 3 /ton in June with a gained output ratio (GOR) of 2.7. The cost analysis shows that the specific cost of freshwater produced from the proposed desalination plant using HR loop is about $1.49/m 3 when Solar Energy runs the proposed system. This particular water cost could decline to $0.54/m 3 when waste heat is used.